Biomimetic Photonic Multiform Composite for High‐Performance Radiative Cooling. Issue 22 (9th September 2021) - Liu, Xianghui; Xiao, Chengyu; Wang, Pan; Yan, Max; Wang, Huifen; Xie, Peiwen; Liu, Gang; Zhou, Han; Zhang, Di; Fan, Tongxiang
Abstract: Nanostructures on bodies of biological inhabitants in severe environments can exhibit excellent thermoregulation, which provide inspirations for artificial radiative cooling materials. However, achieving both large‐scale manufacturing and flexible form‐compatibility to various applications needs remains as a formidable challenge. Here a biomimetic strategy is adopted to design a thermal photonic composite inspired by the previously unexplored golden cicada's evolutionarily optimized thermoregulatory ability. A microimprint combined with phase separation method is developed for fabricating a biomimetic photonic material made of porous polymer–ceramic composite profiled in microhumps. The composite demonstrates high solar reflectance (97.6%) and infrared emissivity (95.5%) in atmospheric window, which results in a cooling power of 78 W m −2 and a maximum subambient temperature drop of 6.6 °C at noon. Moreover, the technique facilitates multiform manufacturing of the composites beyond films, as demonstrated by additive printing into general 3D structures. This work offers biomimetic approach for developing high‐performance thermal regulation materials and devices. Abstract : A biomimetic strategy for daytime radiative cooling is developed inspired by the thermoregulation of golden cicadae. Fabricated by microimprint and phase separation, a porous polymer–ceramic composite with enhanced solar reflectance (97.6%) and mid‐infrared emissivity (95.5%) achieves maximum subambient temperature drop of 6.6 °C. This technique further facilitates multiform manufacturing including 3D printing for complicated stereo architectures in room temperature.